Analytical fragility assessment of structures under earthquake and tsunami loads: a case study on the Colombian Pacific coast - Rivas, Miguel (2019)
This article presents a procedure for the fragility assessment of structures in response to earthquake and tsunami loads using the accumulation of inelastic displacement as a measure of damage. The proposed methodology considers a non-linear static analysis (pushover) for the case of the earthquake and a non-linear static load for the case of the tsunami, taking as starting point the final state of the structure after the occurrence of an earthquake. However, since the impulse force is the critical component of the tsunami load, a simplified approximation in terms of the flood depth is used to estimate the total of the tsunami load. By combining the effect of earthquake and tsunami hazard, a function is obtained relating the spectral acceleration of the earthquake, the flood depth of the tsunami and the drift. Finally, a case study of timber houses located in the municipality of San Andrés de Tumaco at the Colombian Pacific coast is analyzed to assess de proposed methodology. The fragility curve obtained allows a new approach to Multi-hazard risk assessment in areas susceptible to the occurrence of earthquake and tsunami.